2022
DOI: 10.1186/s13098-021-00781-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of subclinical left ventricle myocardial dysfunction using global myocardial work in type 2 diabetes mellitus patients with preserved left ventricle ejection fraction

Abstract: Background The purpose of this study was to assess subclinical left ventricle (LV) myocardial dysfunction using global myocardial work (MW) in type 2 diabetes mellitus (T2DM) patients with preserved left ventricle ejection fraction (LVEF). Methods Sixty T2DM patients and 60 normal controls were enrolled in the study. Apical 4-, 3- and 2-chamber views were acquired by two-dimensional echocardiography. Peak systolic myocardial global longitudinal str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Wang (8) and Yan (9) have suggested that individuals with T2DM exhibit increased global wasted work (GWW) and decreased global work efficiency (GWE) compared to the general population. However, Wang et al found no statistically significant differences in GWW and GWE between the two groups (10). In the present study, we used a non-invasive myocardial work technique to obtain myocardial work parameters and compared them with conventional ultrasound parameters after excluding potential confounding factors.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…Wang (8) and Yan (9) have suggested that individuals with T2DM exhibit increased global wasted work (GWW) and decreased global work efficiency (GWE) compared to the general population. However, Wang et al found no statistically significant differences in GWW and GWE between the two groups (10). In the present study, we used a non-invasive myocardial work technique to obtain myocardial work parameters and compared them with conventional ultrasound parameters after excluding potential confounding factors.…”
Section: Introductionmentioning
confidence: 79%
“…Conversely, GWW reflects the LV myocardial work done to hinder ventricular ejection and relaxation by making myocardial lengthening during systole and shortening during diastole. GWE can be calculated as GCW/(GCW+GWW) ( 10 , 23 ). The Tei index is the ratio of the sum of isovolumic contraction time and isovolumic relaxation time to the ejection time, and it reflects the overall systolic and diastolic function of the LV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was recently discovered that LVGLS can be used to supplement LVEF, particularly in patients with HFpEF [ 3 , 6 , 49 ]. Decreased LVGLS is a marker of myocardial dysfunction that indicates subclinical LV dysfunction before clinical symptoms develop [ 3 , 50 , 51 ]. Furthermore, strain echocardiography can detect early diastolic dysfunction by calculating left atrial strain [ 52 , 53 ].…”
Section: Evaluation Of Cardiovascular Diseases In Patients With Diabe...mentioning
confidence: 99%